Current Status and Future Targeted Therapy in Adrenocortical Cancer - Alyateem, George; Nilubol, Naris (Frontiers in Endocrinology, 2021)
Adrenocortical carcinoma (ACC) is a rare malignancy with a poor prognosis. The current treatment standards include complete surgical resection for localized resectable disease and systemic therapy with mitotane alone or in combination with etoposide, doxorubicin, and cisplatin in patients with advanced ACC. However, the efficacy of systemic therapy in ACC is very limited, with high rates of toxicities. The understanding of altered molecular pathways is critically important to identify effective treatment options that currently do not exist. In this review, we discuss the results of recent advanced in molecular profiling of ACC with the focus on dysregulated pathways from various genomic and epigenetic dysregulation. We discuss the potential translational therapeutic implication of molecular alterations. In addition, we review and summarize the results of recent clinical trials and ongoing trials.